Diradical Organic One‐Dimensional Polymers Synthesized on a Metallic Surface. (7th August 2020) - Sánchez‐Grande, Ana; Urgel, José I.; Cahlík, Aleš; Santos, José; Edalatmanesh, Shayan; Rodríguez‐Sánchez, Eider; Lauwaet, Koen; Mutombo, Pingo; Nachtigallová, Dana; Nieman, Reed; Lischka, Hans; de la Torre, Bruno; et al.
Abstract: We report on the synthesis and characterization of atomically precise one‐dimensional diradical peripentacene polymers on a Au(111) surface. By means of high‐resolution scanning probe microscopy complemented by theoretical simulations, we provide evidence of their magnetic properties, which arise from the presence of two unpaired spins at their termini. Additionally, we probe a transition of their magnetic properties related to the length of the polymer. Peripentacene dimers exhibit an antiferromagnetic ( S =0) singlet ground state. They are characterized by singlet–triplet spin‐flip inelastic excitations with an effective exchange coupling ( J eff ) of 2.5 meV, whereas trimers and longer peripentacene polymers reveal a paramagnetic nature and feature Kondo fingerprints at each terminus due to the unpaired spin. Our work provides access to the precise fabrication of polymers featuring diradical character which are potentially useful in carbon‐based optoelectronics and spintronics. Abstract : The synthesis and characterization of atomically precise one‐dimensional diradical peripentacene polymers on a Au(111) surface is reported. By means of high‐resolution scanning probe microscopy complemented by theoretical simulations, evidence of their magnetic properties is provided, which arise from the presence of two unpaired spins at their termini.